Metabolic Disorders and Risk of Portal Vein Thrombosis in Liver Cirrhosis: A Systematic Review and Meta-Analysis - Li, Jiao; Wang, Qiong; Yang, Mei; Sun, Xiaobin (Turkish Journal of Gastroenterology, 2022)
Portal vein thrombosis is considered to be an indicator of worse outcomes in patients with hepatic cirrhosis. More and more evidence shows that metabolic disorders are noticeable pro-thrombotic factors. However, whether or not metabolic disorders increase the risk of cirrhotic portal vein thrombosis is controversial. We aim to quantify the magnitude of the association between metabolic disorders and the risk of cirrhotic portal vein thrombosis. Databases were searched for papers to identify studies in which metabolic disorders were compared in liver cirrhosis with or without portal vein thrombosis. Based on data from the eligible studies, metabolic disorders related to portal vein thrombosis included diabetes mellitus, nonalcoholic fatty liver disease, hypercholesterolemia, and body mass index. Pooled adjusted odds ratios with 95% CIs were calculated. Data for 22 studies with a total of 57 371 portal vein thrombosis cases and 3 979 015 participants were included. Statistically significant pooled odds ratios for portal vein thrombosis were obtained for diabetes mel- litus (odds ratio 1.80, 95% CI 1.42-2.28), nonalcoholic fatty liver disease (odds ratio 1.61, 95% CI 1.34-1.95), and hypercholesterolemia (odds ratio 3.59, 95% CI 1.83-7.03). Body mass index was likely irrelevant with cirrhotic portal vein thrombosis (odds ratio 1.01, 95% CI 0.87-1.17), both in overall and subgroup meta-analyses. Significant heterogeneities among studies were observed, except for the hypercholesterolemia group. Metabolic disorders, such as diabetes mellitus, nonalcoholic fatty liver disease, and hypercholesterolemia, increased the risk of portal vein thrombosis in cirrhotic patients by 1.80-fold, 1.61-fold, and 3.59-fold, respectively. Body mass index did not appear to be a risk predictor of cirrhotic portal vein thrombosis. Further, well-designed clinical and mechanistic studies are required to strengthen the arguments, especially in obese patients. Cite this article as: Li J, Wang Q, Yang M, Sun X. Metabolic disorders and risk of portal vein thrombosis in liver cirrhosis: A systematic review and meta-analysis. Turk J Gastroenterol. 2022;33(7):541-553.